2023
DOI: 10.1109/tbme.2022.3204506
|View full text |Cite
|
Sign up to set email alerts
|

ERP Detection Based on Smoothness Priors

Abstract: Detection of event-related potentials (ERPs) in electroencephalography (EEG) is of great interest in the study of brain responses to various stimuli. This is challenging due to the low signal-to-noise ratio of these deflections. To address this problem, a new scheme to detect the ERPs based on smoothness priors is proposed. Methods: The problem is considered as a binary hypothesis test and solved using a smooth version of the generalized likelihood ratio test (SGLRT). First, we estimate the parameters of proba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another simple strategy to enhance ERP is to pass the data through a bandpass filter (BPF). ERPs have slower fluctuations compared to wide-band background EEG (0-60 Hz) [10]. Therefore, applying a BPF to raw data can improve the SNR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another simple strategy to enhance ERP is to pass the data through a bandpass filter (BPF). ERPs have slower fluctuations compared to wide-band background EEG (0-60 Hz) [10]. Therefore, applying a BPF to raw data can improve the SNR.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the whitening of EEG data can improve P300 detection in a subsequent phase. In [10], the authors formulated a P300 detection method based on temporal smoothness priors, enabling the incorporation of spatial distribution of P300 signals through a structural matrix as well. In [19], the authors proposed a modified spatiotemporal filter that extracted the data windows along both space and time dimensions to maximize the P300 SNR.…”
Section: Introductionmentioning
confidence: 99%